The "Out of Africa" hypothesis, human genetic diversity, and comparative economic development - Quamrul Ashraf; Oded Galor (Institute for the Study of Labor (IZA), 2012)
This research argues that deep-rooted factors, determined tens of thousands of years ago, had a significant effect on the course of economic development from the dawn of human civilization to the contemporary era. It advances and empirically establishes the hypothesis that in the course of the exodus of Homo sapiens out of Africa, variation in migratory distance from the cradle of humankind to various settlements across the globe affected genetic diversity and has had a direct long-lasting effect on the pattern of comparative economic development that could not be captured by contemporary geographical, institutional, and cultural factors. In particular, the level of genetic diversity within a society is found to have a hump-shaped effect on development outcomes in the pre-colonial era, reflecting the trade-off between the beneficial and the detrimental effects of diversity on productivity. Moreover, the level of genetic diversity in each country today (i.e., genetic diversity and genetic distance among and between its ancestral populations) has a similar non-monotonic effect on the contemporary levels of income per capita. While the intermediate level of genetic diversity prevalent among the Asian and European populations has been conducive for development, the high degree of diversity among African populations and the low degree of diversity among Native American populations have been a detrimental force in the development of these regions. Further, the optimal level of diversity has increased in the process of industrialization, as the beneficial forces associated with greater diversity have intensified in an environment characterized by more rapid technological progress.
urn:nbn:de:101:1-2012042311304
Keywords: N10; N30; N50; O10; O50; Z10; 330; Out of Africa hypothesis; human genetic diversity; comparative development; population density; Neolithic Revolution; land productivity; Malthusian stagnation; Anthropologie; Menschen; Mobilität; Geographie; Entwicklung; Vergleich; Bevölkerung; Welt